College Physics - Urone, Paul Peter; Hinrichs, Roger; Dirks, Kim; Open Textbook Library (Open Textbook Library, 2012)
This introductory, algebra-based, two-semester college physics book is grounded with real-world examples, illustrations, and explanations to help students grasp key, fundamental physics concepts. This online, fully editable and customizable title includes learning objectives, concept questions, links to labs and simulations, and ample practice opportunities to solve traditional physics application problems. OpenStax College has compiled many resources for faculty and students, from faculty-only content to interactive homework and study guides.
1. Introduction: The Nature of Science and Physics -- 2. Kinematics -- 3. Two-Dimensional Kinematics -- 4. Dynamics: Force and Newton's Laws of Motion -- 5. Further Applications of Newton's Laws: Friction, Drag, and Elasticity -- 6. Uniform Circular Motion and Gravitation -- 7. Work, Energy, and Energy Resources -- 8. Linear Momentum and Collisions -- 9. Statics and Torque -- 10. Rotational Motion and Angular Momentum -- 11. Fluid Statics -- 12. Fluid Dynamics and Its Biological and Medical Applications -- 13. Temperature, Kinetic Theory, and the Gas Laws -- 14. Heat and Heat Transfer Methods -- 15. Thermodynamics -- 16. Oscillatory Motion and Waves -- 17. Physics of Hearing -- 18. Electric Charge and Electric Field -- 19. Electric Potential and Electric Field -- 20. Electric Current, Resistance, and Ohm's Law -- 21. Circuits and DC Instruments -- 22. Magnetism -- 23. Electromagnetic Induction, AC Circuits, and Electrical Technologies -- 24. Electromagnetic Waves -- 25. Geometric Optics -- 26. Vision and Optical Instruments -- 27. Wave Optics -- 28. Special Relativity -- 29. Introduction to Quantum Physics -- 30. Atomic Physics -- 31. Radioactivity and Nuclear Physics -- 32. Medical Applications of Nuclear Physics -- 33. Particle Physics -- 34. Frontiers of Physics
In English.
Description based on print resource
Keywords: Science -- Textbooks; Physics -- Textbooks